Free-breathing multislice native myocardial T1 mapping using the slice-interleaved T1 (STONE) sequence - Weingärtner, Sebastian (Magnetic resonance in medicine, 2014)
Purpose: To develop a novel pulse sequence for free-breathing, multislice, native myocardial T1 mapping. Methods: The slice-interleaved T1 (STONE) sequence consists of multiple sets of single-shot images of different slices, acquired after a single nonselective inversion pulse. Each slice is only selectively excited once after each inversion pulse to allow sampling of the unperturbed longitudinal magnetization in the adjacent slices. For respiratory motion, a prospective slice-tracking respiratory navigator is used to decrease through-plane motion followed by a retrospective image registration to reduce in-plane motion. STONE T1 maps were calculated using both a two-parameter and three-parameter fit model. The accuracy and precision of the STONE sequence for different T1, T2, and inversion pulse efficiency were studied using numerical simulations and phantom experiments. T1 maps from 14 subjects were acquired with the STONE sequence and T1s were compared to the MOdified Look-Locker Inversion recovery sequence (MOLLI). Results: In numerical simulations and phantom experiments, the STONE sequence using a two-parameter fit model yields more accurate T1 times compared to MOLLI, with similar high precision. The three-parameter fit model further improves the accuracy, but with a reduced precision. The native myocardial T1 times were higher in the STONE sequence using two- or three-parameter fit compared to MOLLI. The standard deviation of the T1 times was lower in the STONE T1 maps with a two-parameter fit compared with MOLLI or a three-parameter fit. Conclusion: The STONE sequence allows accurate and precise quantification of native myocardial T1 times with the additional benefit of covering the entire ventricle.